Regional Government PR Synergy in Countering Hoaxes and Enhancing Digital Literacy in Bengkulu: A Phenomenological Study - Tri Wahyuniarti; Alib Prihantoro Putro; Dyah Noor Intan (CHANNEL: Jurnal Komunikasi, 2026)
The spread of hoaxes on digital platforms has become a significant challenge in Indonesia, particularly in Bengkulu Province. This study examines the role of local government public relations, media, and influencers in combating hoaxes and improving digital literacy among the public. Employing a qualitative approach with a phenomenological design, this research explores the collaborative strategies and lived experiences of key stakeholders. Data were collected through in-depth interviews, focus group discussions, and document analysis. The findings highlight the importance of collaboration between the government, media, and influencers in creating effective digital literacy campaigns. The study reveals a critical communication gap, where government PR has not fully optimized the role of influencers as strategic "opinion leaders" to reach younger demographics. While influencers demonstrate high engagement, the absence of standardized ethical guidelines, like those of traditional journalism, poses challenges for information accuracy. Key Challenges identified include low levels of digital literacy, insufficient regulatory frameworks, and the uncontrolled influence of social media actors. The findings underscore that cross-sectoral collaboration is essential for effective digital literacy campaigns, leveraging the emotional proximity of local media and the broad reach of influencers among younger audiences. The study concludes that a robust regulatory framework for influencers, combined with structured and continuous digital literacy programs, is essential to strengthen public resilience against hoaxes. These findings contribute to the development of government PR strategies in navigating the post-truth era at a regional level.